Numerical study on performance optimization and flow mechanism of a new cyclone separator - Mengjing Feng; Chengmin Gui; Yangfan Zhou; Zhigang Lei (Green Chemical Engineering)
This study proposed a new cyclone separator, using a designed nozzle inside the traditional cyclone separator, which significantly improved the efficiency of separating fine particles while maintaining an essentially unchanged pressure drop. Firstly, computational fluid dynamics (CFD) was used to compare the flow characteristics of the new cyclone separator with those of the traditional cyclone separator. On this basis, this study comprehensively investigated the pressure drop and separation efficiency of two separators under varying working conditions. The new separator achieved a separation efficiency for particles with a particle size of 1 μm that was approximately 45% higher than that of the traditional separator when the inlet velocity was 2–10 m/s. Besides, the pressure drop of the cyclone separator remained unchanged while the separation efficiency increased by 46% at an inlet flow rate of 2 m/s. The influence of the outlet area of the nozzle inside the new cyclone separator on the separation efficiency and pressure drop was analyzed, and the outlet area of the nozzle with the best overall performance was determined. It was found that the overall performance of the new cyclone separator is optimal when the nozzle outlet area is S/f = 2 cm. Finally, an energy-saving cyclone separator with high separation efficiency was developed through an in-depth study of the variation of particle motion configuration with time. It is worth noting that this study provides a guidance for the flow field analysis and geometry optimization of new gas-solid separators, not limited to cyclone separators.